Monetary and fiscal policy coordination and macroeconomic stabilization. A theoretical analysis - Luca Lambertini; Riccardo Rovelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
We examine the relations between monetary and fiscal policies in the process of macroeconomic stabilization.Our model suggests that each policimaker prefers to be the second mover in a "Stakelberg" situation, i.e. where one policy makers precommits its policy choce. At the same time, both Stakelberg solutions are preferable, for each policumaker, to the Nash solution. We argue that there is a natural way to choose among two Stakelberg games. The solution implies that the government acts as a leader and sets fiscal policy according to the minimization of the Social Welfare Function (which fully internalizes also the objective of price stability). This optimal solution mirrors the existing institutional arrangements, where fiscal policy decisions ate typically taken before, and less frequently than monetary policy decisions. We interpret our results in relation to the debate on monetary-fiscal coordination in EMU and on the role of the Stability and Growth Pact. We argue that a coordination mechanism along the lines of the Broad Economic Policy is desirable.
Keywords: 330